Effect of home-based online training and activity feedback on oxygen uptake in patients after surgical cancer therapy: a randomized controlled trial - Falz, Roberto; Bischoff, Christian; Thiemer, René; Tegtbur, Uwe; Hillemanns, Peter; Stolzenburg, Jens-Uwe; Aktaş, Bahriye; Bork, Ulrich; Weitz, Jürgen; Lässing, Johannes; Lepschy, Christian; Voß, Johannes; et al. (BMC medicine, 2023)
Cardiac output, Activity feedback, Adherence, Body composition, Strength-endurance training, Homebased exercise